Recurrent and capital estimates of the Lagos State government 2002 - Ministry of Economic Planning and Budget (Lagos : Ministry of Economic Planning and Budget, 2002)
This is the Lagos State 2002 budget proposal tagged "The Budget of Pragmatic Consolidation", presented to the Lagos State House of Assembly by the Lagos State governor, Chief Bola Ahmed Tinubu on Wednesday 19th December, 2002.
rpm 20/04/2017
Loans
Keywords: Economic Planning; Economics; Economic Planning -- Lagos State; Budget; Economic Planning and Budget; Lagos